Desarrollo de un agente inteligente para dispositivos móviles android que permita llevar los ingresos y egresos económicos de una persona. - Solano Cabrera, John Patricio (2016)
Nowadays many of us are involved in economic dilemmas because we don’t have a culture of savings, this causes that the expenses are greater than the income, therefore it destabilizes the economic situation within families, also should be mentioned that people who take personal care in their spending consume time doing this. The role of new technologies is to help and provide a good life for all people that is why the current degree work is aimed at solving and help to control in an efficient way our income and expenses suggesting ideas on how to save and contributing to analyze data that helps to reveal the priorities of expenses. The current degree work focuses on intelligent agents on Android mobile devices that use JADE-LEAP library developed in Java, and the implementation of algorithms that help to evaluate efficiently the budget of a person. For the development of this application was used the XP Extreme Programming Methodology and for the development of the agent was used the Methodology GAIA for deliberative intelligent agents.